How do Differing Standards Increase Trade Costs? The Case of Pallets - Raballand, Gaël (World Bank, Washington, DC, 2012)
The pallet is a platform used for storing, handling, and transporting products. There are hundreds of different pallet sizes around the world. The case of pallets is examined to illustrate the impact of multiplicity of standards on trade costs. We select this case because pallets are used all around the world, pallet standards are not too sophisticated, and data on the impact of pallet standards are to some extent available. The paper examines why there are so many different pallet sizes, the associated trade costs and the reasons why countries have not harmonized pallet sizes to eliminate such costs. It then presents options for exporters to mitigate the adverse effects of standards multiplicity while complying with destination markets' standard requirements. The range of options is limited in the case of exporters from less developed countries because of the lack of rental and exchange pallet markets. To mitigate the costs of this multiplicity of standards, the World Bank's strategy should be divided in two directions: to develop awareness of costs related to the multiplicity of standards and to support actively harmonization at the global level (within International Organization for Standardization) and at the regional level (within regional cooperation agreements).